Use of extracorporeal membrane oxygenation in patients with acute high-risk pulmonary embolism: a case series with literature review - You Na Oh; Dong Kyu Oh; Younsuck Koh; Chae-Man Lim; Jin-Won Huh; Jae Seung Lee; Sung-Ho Jung; Pil-Je Kang; Sang-Bum Hong (Acute and Critical Care, 2019)
Background Although extracorporeal membrane oxygenation (ECMO) has been used for the treatment of acute high-risk pulmonary embolism (PE), there are limited reports which focus on this approach. Herein, we described our experience with ECMO in patients with acute high-risk PE. Methods We retrospectively reviewed medical records of patients diagnosed with acute high-risk PE and treated with ECMO between January 2014 and December 2018. Results Among 16 patients included, median age was 51 years (interquartile range [IQR], 38 to 71 years) and six (37.5%) were male. Cardiac arrest was occurred in 12 (75.0%) including two cases of out-of-hospital arrest. All patients underwent veno-arterial ECMO and median ECMO duration was 1.5 days (IQR, 0.0 to 4.5 days). Systemic thrombolysis and surgical embolectomy were performed in seven (43.8%) and nine (56.3%) patients, respectively including three patients (18.8%) received both treatments. Overall 30-day mortality rate was 43.8% (95% confidence interval, 23.1% to 66.8%) and 30-day mortality rates according to the treatment groups were ECMO alone (33.3%, n=3), ECMO with thrombolysis (50.0%, n=4) and ECMO with embolectomy (44.4%, n=9). Conclusions Despite the vigorous treatment efforts, patients with acute high-risk PE were related to substantial morbidity and mortality. We report our experience of ECMO as rescue therapy for refractory shock or cardiac arrest in patients with PE.